Design Development and Analysis of Various Component of Four Wheel Drive - Anjikar, Prof. A. D.; Pachpor, Mr.Manthan; Mate, Mr.Devesh; Bhagat, Mr.Ankit (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
This paper concentrates on explaining the Design and Analysis aspects of making a Go Kart for Students Kart Design. This report explains objectives, assumptions and calculations made in designing of Go Kart.